Refusal Strategies on Request Speech Acts by Indonesian University Students - Nuri Emmiyati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate how Indonesian EFL learners realize refusal strategies in response to request speech acts across different communicative contexts, with particular attention to the influence of sociocultural norms and pragmatic competence.The study employed a qualitative descriptive research design to explore the context-sensitive nature of refusal speech acts. Data were collected through an open-ended Discourse Completion Test (DCT) consisting of ten hypothetical scenarios adapted from previous studies. The participants were 40 Indonesian undergraduate students majoring in English Education, selected through purposive sampling based on their academic exposure to English. The responses were analyzed using a semantic formula framework to classify refusal strategies into direct and indirect types. The analysis yielded 77 instances of refusal strategies, comprising 34 direct and 43 indirect forms, indicating a clear preference for indirectness. Direct strategies were primarily realized through explicit negation, reasons, and explanations, often accompanied by mitigating elements such as regret. Indirect strategies were more varied and frequently involved complex combinations, with “reason + explanation” and “regret + reason + explanation” emerging as the most dominant patterns. These findings suggest that learners employ multi-layered strategies to balance clarity and politeness in managing face-threatening acts. This study contributes to interlanguage pragmatics by providing empirical evidence from the Indonesian EFL context, an area that remains underrepresented in the literature. The findings highlight the importance of integrating explicit pragmatic instruction and context-based learning into EFL curricula to enhance learners’ ability to perform speech acts appropriately across diverse communicative situations.